VARIACIÓN TEMPORAL DE LA ABUNDANCIA EN FAMILIAS DE MOSCAS CARROÑERAS (DIPTERA, CALYPTRATAE) EN UN VALLE ANDINO ANTROPIZADO DE COLOMBIA - Amat, Eduardo; Ramírez-Mora, Manuel A.; Buenaventura, Eliana; Gómez-Piñerez, Luz Miryam (Instituto de Ecología, A.C., 2013)
In temperate studies on carrion flies assemblages is widely accepted that Calliphoridae followed by Sarcophagidae, Muscidae and Fanniidae are the most abundant families in terms of abundance. In the Neotropical region, consideration on this matter had been little studied. During a one-year survey, the abundance variation of these families assemblage of carrion flies in an anthropized Andean valley located in the province of Antioquia, was studied. From February 2010 to February 2011 two monthly sampling per site were performed, Van Someren Rydon traps baited with fish and chicken were settled in four localities, one per cardinal point with different landscape use. A total number of 33838 flies were collected distributed as follow: Calliphoridae (39%), Sarcophagidae (23%), Fanniidae (18%), Muscidae (16%), and small fraction of other dipteran families (4%). This trend in the families abundance was observed during the complete year except in May, March and August when sarcophagids were the most abundant. It is remarkable the alternate half-year abundance of Muscidae and Fannidae. No significance differences in flies’ abundance were observed according the climatic season, and sampling locality. Differences in flies abundance were found by month sampled where an increase pattern in the last months were evident. Differences also were found in family rank assessed, being Calliphoridae the most frequent. Accumulate number of Sarcophagidae contrast with others studies in tropical ecosystem where the second more frequent family is Muscidae probably due to the type and decomposition stage of the bait.